2016
DOI: 10.20341/gb.2016.004
|View full text |Cite
|
Sign up to set email alerts
|

Upper and uppermost Famennian (Devonian) brachiopods from north-western France (Avesnois) and southern Belgium

Abstract: ABSTRACT. Uppermost Famennian (Strunian) brachiopods are relatively frequent in the mixed carbonate-siliciclastic succession of north-western France (Avesnois) and southern Belgium, but they remain relatively poorly known, partly due to their generally deficient preservation. In an effort to revise the material described by Dehée in the first half of the 20 th century, which were mostly recovered from the uppermost Famennian Etroeungt Formation in the Avesnois but also most probably within the underlying Epine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Remarks. Although this species was overlooked by Mottequin (2019), it is the only discinid described from the uppermost Famennian (Strunian) of the Namur-Dinant Basin and should be thus added to Mottequin & Brice's (2016) review of Strunian brachiopods from this area. Note that Dehée (1929) did not report discinids in the contemporaneous succession of the Avesnois (northern France), but Mortelmans (1969) reported the occurrence of representatives of the genus Orbiculoidea d'Orbigny, 1847 within the Etroeungt Formation (Tournai area).…”
Section: Order Lingulida/superfamily Discinoideamentioning
confidence: 99%
“…Remarks. Although this species was overlooked by Mottequin (2019), it is the only discinid described from the uppermost Famennian (Strunian) of the Namur-Dinant Basin and should be thus added to Mottequin & Brice's (2016) review of Strunian brachiopods from this area. Note that Dehée (1929) did not report discinids in the contemporaneous succession of the Avesnois (northern France), but Mortelmans (1969) reported the occurrence of representatives of the genus Orbiculoidea d'Orbigny, 1847 within the Etroeungt Formation (Tournai area).…”
Section: Order Lingulida/superfamily Discinoideamentioning
confidence: 99%
“…These external features are suggestive of Cleiothyridina rather than Crinisarina Cooper and Dutro, 1982 which is more strongly uniplicate and pentagonal in outline. Although markedly smaller, this specimen might be related to the elongate specimens identified as Cleiothyridina struniensis (Dehée, 1929) by Halamski and Baliński (2009) from the most probably uppermost Famennian of the South Polish shelf [see also discussion in Mottequin and Brice (2016) about the generic assignment of Dehée's species]. Occurrence.…”
Section: Superfamily Wellerelloidea Licharew (Inmentioning
confidence: 83%
“…In Europe, they were reported at least in the middle Famennian of the Holy Cross Mountains of Poland (Biernat and Racki, 1986a) but are absent there from the top of the Famennian (Halamski and Baliński, 2009). They seem to be unrecorded in the upper and uppermost Famennian shallower deposits like in the Franco-Belgian Basin (Dehée, 1929;Mottequin and Brice, 2016) or in the Cantabrian Mountains in Spain (García-Alcalde, 1996). The record of terebratulides by Dantz (1893) (see also Paul, 1937) within (at least) the upper Famennian of the Aachen area (Germany), which corresponds to the eastern extension of the Franco-Belgian Basin, needs to be confirmed.…”
Section: Brachiopod Changes At the Devonian-carboniferous Boundarymentioning
confidence: 98%
“…Finally, because the generic name introduced by Sartenaer (1970) had already been used by Luehe (1911) for a genus of parasitic worms (Acanthocephala), Özdikmen (2008) introduced the new genus name Sartenaerus for Centrorhynchus sensu Sartenaer (1970). Mottequin et al (2014) indicated that the genus Centrorhynchus (= Sartenaerus ) first occurs in the middle Famennian, as observed in Western Europe (Mottequin and Brice, 2016), but the brachiopod record from Armenia establishes that it was already present in the lower part of this stage.…”
Section: Systematic Paleontologymentioning
confidence: 99%